Safe and healthy school environments - Frumkin, Howard (New York ; Oxford : Oxford University Press, 2006)
Exploring the school environment using the methods and perspectives of environmental health science, this book covers various aspects of the school environment, including air quality, toxic hazards, food, physical activity, violence, transportation, disaster preparedness, and health services.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School hygiene -- United States; School environment -- United States; Schools -- United States -- Safety measures